2008
DOI: 10.1002/ps.1564
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in the molecular discrimination of formae speciales of Fusarium oxysporum

Abstract: Rapid and reliable detection and identification of potential plant pathogens is required for taking appropriate and timely disease management measures. For many microbial species of which all strains generally are plant pathogens on a known host range, this has become quite straightforward. However, for some fungal species this is quite a challenge. One of these is Fusarium oxysporum Schlechtend:Fr., which, as a species, has a very broad host range, while individual strains are usually highly host-specific. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
119
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(123 citation statements)
references
References 66 publications
4
119
0
Order By: Relevance
“…Classifying Fusarium is always difficult but a FUSARIUM ID v. 1.0, a publicly available database based on partial translation elongation factor 1 alpha (TeF) DNA sequences, which can be used as a phylogenetic marker has been created (Geiser et al 2004). The recent development in the molecular discrimination of Fox was reviewed by Lievens et al (2008). Recently few studies have demonstrated the efficient use of markers to detect and assess the genetic diversity of Foc (Dita et al 2010;Groenewald et al 2006;Ingle and Ingle 2013;Leong et al 2010;Li et al 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…Classifying Fusarium is always difficult but a FUSARIUM ID v. 1.0, a publicly available database based on partial translation elongation factor 1 alpha (TeF) DNA sequences, which can be used as a phylogenetic marker has been created (Geiser et al 2004). The recent development in the molecular discrimination of Fox was reviewed by Lievens et al (2008). Recently few studies have demonstrated the efficient use of markers to detect and assess the genetic diversity of Foc (Dita et al 2010;Groenewald et al 2006;Ingle and Ingle 2013;Leong et al 2010;Li et al 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…could lead to underestimating the actual population of the fungus (Black and Foarde, 2007;Martin-Laurent et al, 2001). SCAR markers derived from an RAPD assay have been used to detect different organisms at isolate or strain levels, such as Gliocladium catenulatum (Paavanen-Huhtala et al, 2000) and Fusarium oxysporum (del Mar Jiménez-Gascó and Jiménez-Díaz, 2003;Pasquali et al, 2006;Lievens et al, 2008). In addition, SCAR markers derived from an RAPD assay have been also previously reported and used to detect different Trichoderma species or strains in different samples with varying detection limits.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the specific DNA fragments detected in a profile may be cut out of the gel and sequenced to obtain a SCAR (Sequence-characterized amplified region), into which specific primers can be designed for a more precise PCR detection. SCAR primers have been used for instance to specifically identify Phytophthora cactorum (Causin et al, 2005), Fusarium subglutinans (Zaccaro et al, 2007) and Guignardia citricarpa (Stringari et al, 2009) in infected plant material; to distinguish among several formae speciales of Fusarium oxysporum (Lievens et al, 2008); to differentiate the bioherbicidal strain of Sclerotinia minor from like organisms (Pan et al, 2010) (Hyun et al, 2009). This technique has also been applied to differentiate fungi isolates according to their host plant (Midorikawa et al, 2008), enzyme production profiles (Saldanha et al, 2007) or geographical origin and chemotypes (Zheng et al, 2009).…”
Section: Random Amplified Polymorphic Dna (Rapd)mentioning
confidence: 99%